Nonalcoholic Fatty Liver Disease in Patients with Normal Body Weight: Epidemiology, Current Issues of Screening and Diagnosis, Approaches to Therapy - I. G. Nikitin; A. V. Starodubova; O. A. Кislyak; T. Yu. Demidova; L. Yu. Ilchenko (Архивъ внутренней медицины, 2025)
Nonalcoholic fatty liver disease (NAFLD) is currently a serious medical and social problem for public health systems due to its high prevalence, potential development of liver cirrhosis (LC) and hepatocellular carcinoma (HCC). In addition, the presence of NAFLD in the patient’s somatic continuum is associated with a significantly higher incidence of cardiovascular events and type 2 diabetes mellitus (T2DM). The most frequent NAFLD is registered in patients with excessive body weight. Patients with normal body weight deserve special attention of researchers and clinicians. Despite the seemingly relatively favorable profile of “metabolic health”, the risk of progression of NAFLD to CKD and HCC, as well as conjugation with cardiovascular events in this group of patients is no less than in the group of patients with NAFLD and high body mass index (BMI). The absence of early symptoms and abnormalities of some indicators characterizing “metabolic health” in patients with NAFLD and normal body weight contributes to late and untimely diagnosis of liver disease and, as a consequence, its progression and the formation of severe vascular and metabolic disorders in the future. In the presented review the authors offer some epidemiological data on the prevalence of NAFLD in patients with normal body weight, variants of the clinical course of NAFLD in the discussed group of patients and propose to make a special emphasis on the obvious need for a much wider involvement of patients with normal body weight in clinical and scientific studies devoted to a detailed study of the pathogenesis, issues of organization of medical care and treatment of NAFLD.